Genetic Analysis and Transfer of Favorable Exotic QTL Alleles for Grain Yield Across D Genome Using Two Advanced Backcross Wheat Populations - Naz, Ali Ahmad; Dadshani, Said; Ballvora, Agim; Pillen, Klaus; Léon, Jens (Frontiers in Plant Science, 2019)
Hexaploid wheat evolved through a spontaneous hybridization of tetraploid wheat (Triticum turgidum, AABB) with diploid wild grass (Aegilops tauschii, DD). Recent genome sequencing found alarmingly low genetic diversity and abundance of repeated sequences across D genome as compared to AB genomes. This characteristic feature of D genome often results in a low recombination rate and abrupt changes in chromosome, which are the major hurdles to utilize the genetic potential of D genome in wheat breeding. In the present study, we evaluated two advanced backcross populations designated as B22 (250 BC2F3:6 lines) and Z86 (150 BC2F3:6 lines) to test their yield potential and to enrich the D genome diversity simultaneously. The populations B22 and Z86 were derived by crossing winter wheat cultivars Batis and Zentos with synthetic hexaploid wheat accessions Syn022L and Syn086L, respectively. These populations were genotyped using SNP markers and phenotyped for yield traits in ten environments in Germany. Marker analysis identified lower recombination rate across D genome as compared to A and B genomes in both populations. Further, we compared the genotype data with the trait grain yield to identify favorable exotic introgressions from synthetic wheat accessions. QTL analysis identified seven and 13 favorable exotic QTL alleles associated with enhancement or at least stable grain yield in populations B22 and Z86, respectively. These favorable introgressions were located on all chromosomes from 1D to 7D. The strongest exotic QTL allele on chromosome 1D at SNP marker RAC875_c51493_471 resulted in a relative increase of 8.6% in grain yield as compared to cultivated allele. The identified exotic introgressions will help to refine useful exotic chromosome segments for their incorporation for improving yield and increasing D genome diversity among cultivated varieties.